LncRNA SNHG11 induces ferroptosis in liver injury cells through miR-324-3p/GPX4 axis-mediated sepsis: SNHG11 induces ferroptosis in liver injury - Yang, Yaopeng; Wang, Anxiu; Zhou, Jun; Yang, Yuanqin; Wu, Haiying (Cellular and Molecular Biology, 2023)
Sepsis is a kind of systemic inflammatory response syndrome caused by infection, which has high morbidity and mortality. Studies have shown that reducing sepsis-related liver injury and restoring liver function can reduce the morbidity and mortality of it. Current clinical treatment methods for sepsis have many disadvantages. Our study aimed to investigate the mechanism of sepsis-induced liver injury and to find a proper therapeutic target for sepsis. In this paper, we have found that when miR-324-3p was overexpressed, the inflammatory infiltration and and ferroptosis in liver injury cells aggravated. Further studies showed that overexpression of miR-324-3p could bind to the 3’-UTR of SNHG11 directly so as to decrease the expression level of SNHG11. Our study indicated that LncRNA SNGH11 can mediate the ferroptosis of liver injury cells induced by sepsis through the miR-324-3p/GPX4 axis. Suggesting that it is a new drug target for clinical treatment of sepsis and sepsis-associated liver injury, then we can improve the survival rate for sepsis patients.